Mapeamento quantitativo dos impactos da gestão democrática no desempenho das escolas públicas no IDEB 2013 - Riscal, José Reinaldo (2016)
The Law of Directives and Bases of National Education. - LDB (Lei No. 9.394 / 1996), in its Article 3, establishes the principles for the implementation of public education, and the Item VIII defines the democratic management of public education, in terms of the law and legislation of education systems as one of these principles. Therefore, we may see that there was, and still is, in Brazil a legal guidance to start a democratic process that seeks to enhance, among other things, the participation of the school professionals and the surrounding community, which also includes students and their families, in the school management, in order to find ways to increase the quality of teaching and learning in public schools. Thus, the real and effective performance of the democratic management needs to be better understood. This study aims to statistically verify and analyze if the democratic management have impacts on the performance of schools in external evaluations, as well as to determine whose place it occupies in the hierarchy of variables that impact on these indicators. To achieve this goal, a literature review was conducted on the topics: school councils, democratic management and external and large scale assessments. In addition, an empirical research through statistical analysis from information from the following sources of official information: School Census (2012 and 2013), Prova Brasil and SAEB raw data (2013), IDEB (2013) and the databases of the Interactive PDDE (2013). The results of this study showed that the highest average IDEB refer to schools where the School Councils always define and validate their pedagogical, financial and administrative aspects. In addition, the construction of a pedagogical project with the participation of the whole school community, parental involvement in School Councils, frequency of School Councils meetings and the selection of the school principal by direct election or public tender are other factors related to democratic management that influence positively IDEB figures.